A cold yield. Cryopreserved oocytes of "social freezing" customers as potential option values for biomedical research. Issue 3 (2nd July 2020) - Friedrich, Alexander
Abstract : While the demand for "social freezing" services has increased significantly in recent years, the number of cryopreserved eggs that are actually being used in treatment remains very low, so far. Both tendencies indicate a continuously growing stock of unused oocytes. In this article, I discuss the possibility that the growing stock could be co-opted to solve the problem of egg procurement especially for biomedical research. As a consequence, the secondary utilization of female fertility resources would become their main form of use. However, this would finally turn the customers of fertility services into unintended productive forces of a cryotechnologically advanced bioeconomy. The paper discusses the risk of a subtle form of exploitation that could be associated with this reproductive service in the future, which will pose further challenges for the practice of informed consent.